Violence et vision : The Dynasts de Thomas Hardy - Laurence Estanove (Cahiers Victoriens et Edouardiens)
The Dynasts, Thomas Hardy’s « epic-drama of the war with Napoleon, » is remarkable in its use of poetic and literary stage directions. Its modernity lies in this hybrid form, but also in its amazing power of visual representation. The « mental spectator » both witnesses the violence of the war and experiences it directly, as Hardy shatters the traditional notions of perspective and point of view in a cinematic and highly innovative way.